Association Between Lumbar Disc Degeneration and Propionibacterium acnes Infection: Clinical Research and Preliminary Exploration of Animal Experiment. Issue 13 (July 2016) - Li, Bo; Dong, Zhe; Wu, Yongchao; Zeng, Ji; Zheng, Qixin; Xiao, Baojun; Cai, Xianyi; Xiao, Zhiyong
Abstract : Study Design: Clinical research and animal experiment. Objective: To investigate whether lumbar disc degeneration is associated with Propionibacterium acnes ( P acnes ) infection. Summary of Background Data: The hypothesis that herniated discs may be infected with P acnes by way of bacteremia is remarkable. This may bring a tremendous change in treatment of lumbar disc herniation (LDH). However, this hypothesis is still controversial. Since P acnes isolated may be related to contamination. Methods: Nucleus pulposus from 22 patients (30 discs) with lumbar disc herniation was collected during discectomy, following aerobic and anaerobic cultures for 10 days. Twenty-four rabbits were divided into four groups. After L3-L6 being exposed, an incision was made into the three discs in groups A and B. While in groups C and D, two random segments were operated. Six weeks later, 0.05 mL of 5 × 10 6  CFU/mL P acnes was inoculated into operated discs in group A and sterile physiological saline in group B. In group C, 0.2 mL of 5 × 10 7  CFU/mL P acnes was injected through ear vein. Sterile saline was used in group D. Six weeks later, MRI was performed. Then, nucleus pulposus and paraspinal muscles were harvested for aerobic and anaerobic cultures. Results: Clinical research: Anaerobic cultures were positive in three cases: two coagulase-negative staphylococci, one particles chain bacterium. No P acnes was found. Staphylococcus epidermidis was isolated in one aerobic culture. Animal experiment: P acnes was found in 11 out of 18 (61%) discs in group A. There was no P acnes found in the other three groups. Conclusion: Degenerated discs were suitable for P acnes growth. This research did not find the evidence of the symptomatic degenerated lumbar discs infected with P acnes or that P acnes could infect the degenerated lumbar discs by way of bacteremia. Level of Evidence: N/A